Interest development, self-related information processing, and practice. Issue 1 (2nd January 2022) - Renninger, K. Ann; Hidi, Suzanne E.
ABSTRACT: Educators have a critical stake in supporting the development of interest—as the presence of interest benefits sustained engagement and learning. Neuroscientific research has shown that interest is distinct from, but overlapping with, self-related information processing, the personally relevant connections that a learner makes to content (e.g., mathematics). We propose that consideration of self-related information processing is critical for encouraging interest development in at least two ways. First, support for learners to make self-related connections to content may provide a basis for the triggering of their interest. Triggered interest encourages individuals to search for more information, and to persevere in understanding material that otherwise might feel meaningless. Second, for learners who already have an initial interest in the content, self-related connections can further promote the deepening of interest through sustained engagement and information search. Background regarding both interest and self-related information processing is provided, and implications for practice are suggested.